Development and clinical application of an enzyme immunoassay for the determination of midregional proadrenomedullin. (6th December 2012) - Suzuki, Yosuke; Itoh, Hiroki; Katagiri, Fumihiko; Sato, Fuminori; Sato, Yukie; Kawasaki, Kanako; Sato, Yuhki; Mimata, Hiromitsu; Takeyama, Masaharu
<x xml:space="preserve">Abstract</x> Adrenomedullin (ADM) is a 52‐amino acid peptide with a variety of physiologic functions such as immunomodulating activity, direct bactericidal activity, maintenance of renal homeostasis, and vasodilatory activity. Midregional proADM (MR‐proADM) is derived from a larger 185‐amino acid precursor peptide, prepro‐adrenomedulin (preproADM), by posttranslational processing. It is suggested to be co‐synthesized with ADM in equimolar amounts and has the advantages over ADM in having a longer half‐life, no bioactivity, and no binding to protein. Therefore, MR‐proADM serves as a surrogate for ADM secretion. In this study, we attempted to develop an enzyme immunoassay (EIA) for quantifying MR‐proADM‐like immunoreactive substance (IS), which is applicable for monitoring plasma MR‐proADM levels. By using β‐d‐galactosidase‐labeled preproADM(83‐94) as a marker antigen, anti‐rabbit IgG‐coated immunoplate as a bound/free separator, and 4‐methylumbelliferyl‐β‐d‐galactopyranoside as a fluorogenic substrate, a sensitive and specific EIA was developed for the quantification of MR‐proADM‐IS in human plasma. The lower limit of quantification was 0.032 pmol/well, and the steep competitive inhibition EIA calibration curve obtained was linear between 0.16 and 10 nmol/L. By using human plasma samples containing 0.2 and 2.0 nmol/L of MR‐proADM, the interassay coefficients of variation (reproducibility) were 10.78% and 8.83%, respectively, and intraassay coefficients were 3.91% and 7.81%. Plasma MR‐proADM‐IS level was significantly higher in patients with chronic renal failure (1.39 ± 0.50 nmol/L) compared with healthy subjects (0.19 ± 0.07 nmol/L). These results suggest that our EIA may be useful to evaluate plasma MR‐proADM levels as a biomarker in various clinical settings. Copyright © 2012 European Peptide Society and John Wiley & Sons, Ltd.